Multilateral approaches to market access negotiations - Sam Laird (World Trade Organization (WTO), 1998)
Market access negotiations in merchandise trade at the multilateral level cover tariffs and non-tariff measures (NTMs). While tariffs have been substantially reduced in earlier rounds, they remain high in certain areas and further reductions involve a number of complex technical issues. Some formulae approaches, not used in the Uruguay Round, seem more favourable to developing countries. Elimination or phased reductions of NTMs in agriculture is one of the main areas for further market access negotiations in trade in goods. However, most NTMs are now the subject to negotiations on the rules under which they may be applied, e.g. in the areas of contingency protection and technical barriers to trade.
Keywords: F13; 330; WTO; market access; trade negotiations; tariffs; non-tariff measures